2016
DOI: 10.1093/femsle/fnw206
|View full text |Cite
|
Sign up to set email alerts
|

The main pigment of the dormantMycobacterium smegmatisis porphyrin

Abstract: Upon transition of Mycobacterium smegmatis into the dormant state, accumulation of a dark brown fluorescent pigment was observed. This pigment gave bright red fluorescence in both cells and the culture medium. Based on H-NMR, MALDI and UV spectra, the fluorescent compounds, extracted from the culture medium as well as from the dormant cells, were concluded to be a mixture of free coproporphyrin III and uroporphyrin III and their corresponding methyl esters. A possible significance of porphyrin pigment accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
4
23
0
2
Order By: Relevance
“…Similarly, the finding of enzymes responsible for porphyrin synthesis (“unique”; Supplementary Table S2 ) in dormant cells is in line with the previously found substantial accumulation of copro- and uroporphyrins in dormant Msm cells ( Nikitushkin et al, 2016 ). Observations indicate that the antioxidant activities of porphyrins act to protect bacteria ( Patel and Day, 1999 ), animal tissues ( Antonova et al, 2010 ), and animal mitochondria ( Castello et al, 2008 ) against reactive oxygen species and toxic nucleophiles ( Fuhrhop, 1974 ).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the finding of enzymes responsible for porphyrin synthesis (“unique”; Supplementary Table S2 ) in dormant cells is in line with the previously found substantial accumulation of copro- and uroporphyrins in dormant Msm cells ( Nikitushkin et al, 2016 ). Observations indicate that the antioxidant activities of porphyrins act to protect bacteria ( Patel and Day, 1999 ), animal tissues ( Antonova et al, 2010 ), and animal mitochondria ( Castello et al, 2008 ) against reactive oxygen species and toxic nucleophiles ( Fuhrhop, 1974 ).…”
Section: Discussionsupporting
confidence: 88%
“…Only one attempt to apply PDI in the treatment of dormant mycobacteria has been performed; dormant M. smegmatis formed in vitro after gradual acidification of the growth medium (Kudykina et al 2011 ) are characterised by a high intracellular concentration of porphyrins. These porphyrins were represented by a mixture of uroporphyrin III and coproporphyrin III and their methyl esters, with cytoplasmic and membrane localisation (Nikitushkin et al 2016 ). These dormant forms were sensitive to illumination with 395-, 475- and 575-nm light, which decreased the CFU by approximately 3 log10 (Shleeva et al 2019 ).…”
Section: Endogenous Photosensitisers For Antimycobacterial Pdimentioning
confidence: 99%
“…It can be assumed that the effect of complete elimination of dormant, "non-culturable" bacteria can be accomplished by factors which produce indirect, harmful effects on bacteria (Kaprelyants et al, 2018). In this regard, we employed a previously discovered phenomenon of the accumulation of free and methylated porphyrins in dormant mycobacteria (Nikitushkin et al, 2016). This finding made it possible to induce the PDI of mycobacteria (Shleeva et al, 2019b(Shleeva et al, , 2020.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, application of physical factors seems to be promising in order to destroy metabolically passive dormant bacterial forms. Recently we found that significant concentrations of the intermediates participating in protoporphyrin biosynthesis were present in dormant forms of M. smegmatis (Nikitushkin et al, 2016), a fast-growing bacterium which is genetically close to M. tuberculosis, These findings suggested that dormant bacteria may be killed by photodynamic inactivation (PDI) when fluorescent porphyrins serve as intracellular photosensitizers. Studies have also demonstrated the photoinactivation of dormant mycobacterial forms in vitro in the rapidly growing, tuberculosis-related pathogenic strain, M. smegmatis (Shleeva et al, 2019b(Shleeva et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%